Lineage-specific mutation of Lmx1b provides new insights into distinct regulation of suture development in different areas of the calvaria - Cabrera Pereira, Angel; Dasgupta, Krishnakali; Ho, Thach-Vu; Pacheco-Vergara, Maria; Kim, Julie; Kataria, Niam; Liang, Yaowei; Mei, Jeslyn; Yu, Jinyeong; Witek, Lukasz; Chai, Yang; Jeong, Juhee (Frontiers in Physiology, 2023)
The calvaria (top part of the skull) is made of pieces of bone as well as multiple soft tissue joints called sutures. The latter is crucial to the growth and morphogenesis of the skull, and thus a loss of calvarial sutures can lead to severe congenital defects in humans. During embryogenesis, the calvaria develops from the cranial mesenchyme covering the brain, which contains cells originating from the neural crest and the mesoderm. While the mechanism that patterns the cranial mesenchyme into bone and sutures is not well understood, function of Lmx1b, a gene encoding a LIM-domain homeodomain transcription factor, plays a key role in this process. In the current study, we investigated a difference in the function of Lmx1b in different parts of the calvaria using neural crest-specific and mesoderm-specific Lmx1b mutants. We found that Lmx1b was obligatory for development of the interfrontal suture and the anterior fontanel along the dorsal midline of the skull, but not for the posterior fontanel over the midbrain. Also, Lmx1b mutation in the neural crest-derived mesenchyme, but not the mesoderm-derived mesenchyme, had a non-cell autonomous effect on coronal suture development. Furthermore, overexpression of Lmx1b in the neural crest lineage had different effects on the position of the coronal suture on the apical part and the basal part. Other unexpected phenotypes of Lmx1b mutants led to an additional finding that the coronal suture and the sagittal suture are of dual embryonic origin. Together, our data reveal a remarkable level of regional specificity in regulation of calvarial development.